Adaptive Elasticity: A Review and Critique of a Bone Tissue Adaptation Model - Cowin, S.C. (Engineering Transactions, 2003)
Living bone is continually undergoing processes of growth, reinforcement and resorption. These processes are termed collectively "remodelling". The remodelling processes in living bone are the mechanisms by which the bone adapts its histological structure to changes in long-term loading. The theory of adaptive elasticity was developed as a model for the mechanical load induced adaptation of bone. Ali three aspects of the theory of adaptive elasticity are reviewed here. These include internal adaptation, surface adaptation and architectural adaptation. The successes of the theory as well as the features of the theory that should now be revised are discussed.